2016
DOI: 10.1038/srep39141
|View full text |Cite
|
Sign up to set email alerts
|

Drosophila microRNA-34 Impairs Axon Pruning of Mushroom Body γ Neurons by Downregulating the Expression of Ecdysone Receptor

Abstract: MicroRNA-34 (miR-34) is crucial for preventing chronic large-scale neurite degeneration in the aged brain of Drosophila melanogaster. Here we investigated the role of miR-34 in two other types of large-scale axon degeneration in Drosophila: axotomy-induced axon degeneration in olfactory sensory neurons (OSNs) and developmentally related axon pruning in mushroom body (MB) neurons. Ectopically overexpressed miR-34 did not inhibit axon degeneration in OSNs following axotomy, whereas ectopically overexpressed miR-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 35 publications
1
16
0
Order By: Relevance
“…4). These findings support the idea that the miR-34-induced MB axon pruning defect in our previous study was probably due to downregulation of the Babo expression 8 . Taken together, our data suggest that babo is a miR-34 target gene, which participates in crucial biological processes such as the axon pruning of MB neurons.…”
Section: Visualization Of Endogenous Babo Expression Using a Babo Ha supporting
confidence: 92%
“…4). These findings support the idea that the miR-34-induced MB axon pruning defect in our previous study was probably due to downregulation of the Babo expression 8 . Taken together, our data suggest that babo is a miR-34 target gene, which participates in crucial biological processes such as the axon pruning of MB neurons.…”
Section: Visualization Of Endogenous Babo Expression Using a Babo Ha supporting
confidence: 92%
“…A single axon projects anteriorly, bifurcates, and then projects both dorsally and medially to form the α and β lobes. Several previous studies have used this technique to investigate whether certain proteins are required to study cell division autonomously for many aspects of axonogenesis, including extension, pathfinding, branching, and/or pruning 10 11 12 13 14 15 16 17 34 .…”
Section: Representative Resultsmentioning
confidence: 99%
“…While the embryonic fly CNS has been used extensively in the past to identify ligands, receptors, and intracellular signaling proteins required for axonal guidance 8 9 , recent work has investigated the ways in which many of these proteins also control pathfinding decisions during later stages of development. Specifically, investigation of mushroom body (MB) and retinal photoreceptor neuron development ( Figure 1 ) has provided insight into the mechanisms that control pathfinding, synapse formation, axon pruning, and several other aspects of neuronal development 10 11 12 13 14 15 16 17 . Photoreceptor neurons connect the fly retina to regions of the adult brain called the lamina and medulla and are critical for relaying visual information to the brain (reviewed by 18 19 ), while mushroom body neurons are centrally located in the fly brain and are required for learning and memory 20 21 .…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have shown that extra dorsal projections can arise due to defects in  neuron remodeling that occur during pupal morphogenesis [41][42][43] . During the larval stages of development, MB  neurons project both dorsally and medially.…”
Section: The Pbap Complex Is Required For Axon Pruning During  Neuromentioning
confidence: 99%
“…This is followed by re-extension of the  neurons medially, but not dorsally, to form the adult  lobe 39 (Figure 4A). The appearance of extra dorsal projections in adult flies is often caused by a failure to prune larval  axons [41][42][43] . To investigate whether the extra dorsal projections we observed were the result of unpruned  neurons, and not from aberrantly formed / neurons, we performed RNAi knockdown using two -neuron specific Gal4 drivers; MB607B-Gal4 (data not shown) and MB009B-Gal4 (Figure 4B) The final observed morphological phenotype, described as faded  lobes, is characterized by normal MB morphology, with a shift in the intensity of fluorescent labeling by GFP.…”
Section: The Pbap Complex Is Required For Axon Pruning During  Neuromentioning
confidence: 99%